A comprehensive review of Cornus officinalis: health benefits, phytochemistry, and pharmacological effects for functional drug and food development - Deng, Wenhui; Liu, Yuchen; Guo, Yaodong; Chen, Jie; Abdu, Hassan Idris; Khan, Muhmmad R. U.; Palanisamy, Chella Perumal; Pei, Jinjin; Abd El-Aty, A. M. (Frontiers in Nutrition, 2024)
Cornus officinalis sieb. et zucc, a deciduous tree or shrub, is renowned for its "Cornus flesh" fruit, which is widely acknowledged for its medicinal value when matured and dried.Leveraging C. officinalis as a foundational ingredient opens avenues for the development of environmentally friendly health foods, ranging from beverages and jams to preserves and canned products. Packed with diverse bioactive compounds, this species manifests a spectrum of pharmacological effects, including anti-inflammatory, antioxidant, antidiabetic, immunomodulatory, neuroprotective, and cardiovascular protective properties. This study employs CiteSpace visual analysis software and a bibliometric analysis platform, drawing upon the Web of Science (WOS) database for literature spanning the last decade. Through a comprehensive analysis of available literature from WOS and Google Scholar, we present a thorough summary of the health benefits, phytochemistry, active compounds, and pharmacological effects of C. officinalis. Particular emphasis is placed on its potential in developing functional drugs and foods. While this review enhances our understanding of C. officinalis as a prospective therapeutic agent, its clinical applicability underscores the need for further research and clinical studies to validate findings and establish safe and effective clinical applications.